Consequences of judging in transitional justice courts - Nyseth Brehm, Hollie (The British journal of criminology, 2021)
Research has found that participation in transitional justice (TJ) is associated with increased social capital and decreased well-being. This article extends this scholarship by examining how TJ mechanisms affect the social capital and well-being of the people who implement them via interviews with 135 Rwandan gacaca court judges. In terms of well-being, judges discuss pride and confidence yet also highlight stress and trauma. In terms of social capital, many judges are now mediators and local leaders, though numerous judges have also experienced grudges from the families of those they sentenced. These negative consequences were particularly prominent among judges with more authority.